AIAA Modeling and Simulation Technologies Conference 2010
DOI: 10.2514/6.2010-7916
|View full text |Cite
|
Sign up to set email alerts
|

Visual Inertial Coherence Zone in the Perception of Heading

Abstract: Knowledge of human motion perception can be applied in the optimization of motion cueing algorithms. In the past it has been shown that some discrepancies between the amplitude or phase of a visual and inertial cue go unnoticed. These acceptable discrepancies are referred to as coherence zones. In the present experiment we investigate whether a coherence zone applies to the direction of visual and inertial motion cues. More specifically, we investigated how much heading of an inertial stimulus may deviate from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Likewise, previous studies have demonstrated that younger adults weight visual and vestibular cues as a function of their relative reliabilities (e.g., Butler et al, 2010; Fetsch et al, 2009), but no previous studies have established whether the same is true for older adults. Finally, whereas a few previous studies have explored the types and magnitude of visual and vestibular spatial conflicts that younger adults will tolerate before they no longer integrate (de Winkel, Correia Gracio, Groen, & Werkhoven, 2010; de Winkel, Katliar, & Bülthoff, 2017; Kaliuzhna et al, 2015), the characteristics of the spatial window of integration are unknown for older adults. In fact, age-related changes to the spatial (rather than temporal) window of integration have generally not been well explored, even when considering other types of cue combinations (e.g., visual-auditory) or tasks (e.g., stimulus detection; de Dieuleveult et al, 2017).…”
mentioning
confidence: 99%
“…Likewise, previous studies have demonstrated that younger adults weight visual and vestibular cues as a function of their relative reliabilities (e.g., Butler et al, 2010; Fetsch et al, 2009), but no previous studies have established whether the same is true for older adults. Finally, whereas a few previous studies have explored the types and magnitude of visual and vestibular spatial conflicts that younger adults will tolerate before they no longer integrate (de Winkel, Correia Gracio, Groen, & Werkhoven, 2010; de Winkel, Katliar, & Bülthoff, 2017; Kaliuzhna et al, 2015), the characteristics of the spatial window of integration are unknown for older adults. In fact, age-related changes to the spatial (rather than temporal) window of integration have generally not been well explored, even when considering other types of cue combinations (e.g., visual-auditory) or tasks (e.g., stimulus detection; de Dieuleveult et al, 2017).…”
mentioning
confidence: 99%
“…The concept was derived from the observation that physically moving observers are unable to detect concurrent visual motion when the amplitude of the visual motion is below a particular threshold [39,40]. CZ have been determined for the amplitude and phase of rotational as well as translation motion [41,42,43,44,45], and also for heading [46,30]. CI models can be said to be formed around an analogous concept, namely the probability that visual and inertial motion with any discrepancy will be attributed to a common cause Pr(C | e V , e I ).…”
Section: Multisensory Distance Estimationmentioning
confidence: 99%